Hubungan Pendidikan Kesehatan Metode Ceramah Dengan Pengetahuan Ibu Nifas Primipara Tentang Perawatan Tali Pusat Bayi Baru Lahir Di PMB Ngadillah Pakis - Afriza Syahbana Destamega; Surachmindari Surachmindari; Asworoningrum Yulindahwati (Poltekkes Kemenkes Malang, 2020)
One cause of the death in infants is the infecti. Tthe infection is caused by a lack of knowledge of the mother on caring the babies especially umbilcal cord care. One of the researchers efforts to increase knowledge about cord care is through the lecturing methods. This method is cheap and also can be repeated easily if the respondents do not understand. The aims of this study is determining the correlation between health education and lecture method with postpartum mothers knowledge about newborn umbilical cord care at PMB Ngadillah Pakis. The design of this study was a Pre Experimental study with a pre and post test design of primiparum postpartum knowledge. The sample used was all primiparum postpartum mothers who met the inclusion criteria of 28 people with the sampling technique used was Total Sampling. Data collection was carried out with a questionnaire about postpartum mother knowledge of cord care were analyzed using the Wilcockson Signed Rank Test. The results of this study showed 89.3 percent knowledge of postpartum mothers in the less category before treatment and 96.4 percent knowledge in either category after treatment. The results of the study were p value 0.001 which showed that the lecture method was able to increase the knowledge of theprimiparum puerperal mother from the less good category so that this method could be used for all postpartum mothers. Health Education with the lecture method can be done as the chosen method to increase the knowledge of primiparum postpartum mothers in performing umbilical cord care.